Injection Rates for Neuroangiography: Results of a Survey - Yousem, David M.; Trinh, Ba Chinh (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: Injection rates have attracted scrutiny because of an incident of an aneurysm rupturing during arteriography. We sought to determine the current injection rates for neuroangiography in the setting of aneurysm evaluation.METHODS: An e-mail survey was distributed to 90 neuroradiology program directors within the United States and Canada. The injection rates and total volumes of contrast material injected for the common carotid, internal carotid, and vertebral arteries were provided for an “average” adult individual evaluated for intracranial aneurysms.RESULTS: Sixty-three (70.0%) program directors replied to the survey. Of these, five perform hand injections only and provided approximate values. The mean injection rates (SD) and total volumes (SD) for common carotid arteries were 7.2 cm3/s (1.8) and 9.9 cm3 (2.0), respectively; for internal carotid arteries, 5.8 cm3/s (1.4) and 7.9 cm3 (1.5); and for vertebral arteries, 5.4 cm3/s (1.2) and 7.8 cm3 (1.7). The modes (rate/total) for the common carotid, internal carotid, and vertebral arteries were 7/12, 6/8, and 5/8, respectively. Forty-eight (81.4%) of 59 respondents did not believe a reduction in current injection rates would lead to a diminution in complications of arteriography.CONCLUSION: The rates of injection of contrast material in the United States for neuroradiologic studies show great variability. It does not seem that reducing arteriographic complications is an impetus to reduce injection rates. The values in this survey can provide “industry norms” for injections in the common carotid, internal carotid, and vertebral arteries if these rates are challenged.